Outside Large Shareholder dan Dividen pada Seasoned Equity Offering (SEO) - Wisudanto, Wisudanto; Ilyassin, Celine; Alfi Nurrita, Mayliya (E-Jurnal Akuntansi; Vol 30 No 4 (2020), 2020)
This study aims to examine the effect of outside large shareholder and corporate governance toward dividend payment in companies that conducted seasoned  equity offering (SEO). Dividend payment may cause a passive shareholder in regard of their right to intervene managerial policy. The research was using a  quantitative method with binary logistic regression as metric. There were 88 nonfinancial companies used within 2007-2017 period, amounting a total of 968 observations. The dependent variable in this research is dividend payment, while the independent variables were large shareholder, outside large shareholder, inside large shareholder and corporate governance. Control variables are ROA, firm size and leverage. The result of this study shows that large shareholder, outside large shareholder and inside large shareholder have significant effect toward dividend payment. Corporate governance has insignificant effect toward dividend payment. Keywords: Large Shareholder; Corporate Governance; Dividen Payment Policy; Seasoned Equity Offering.